Risk Factors for Spontaneous Bacterial Peritonitis in Patients with Liver Cirrhosis and Ascites - Fachrul Razy; Nanang Sukmana; Dharmika Djojoningrat; Sjaifoellah Noer (The Indonesian Society for Digestive Endoscopy, 2002)
Spontaneous bacterial peritonitis (SBP) is one of serious complication of liver cirrhosis. Most of the patient with SBP have severe reduced liver function that clasified as Child Plugh class C. There are other risk factors for SBP such as poor nutritional status, GI bleeding, intravascular catheter insertion, ascites fluid protein concentration of less than 1 g/L, large volume paracentesis, urinary tract infection and respiratory tract infection. The management of SBP is mainly the administration of proper antibiotics. The antibiotic of choice for the emperial treatment is cefotaxim. Keywords: sbp,liver cirrhosis, risk factor, ascites